Catalytic enantioselective OFF ↔ ON activation processes initiated by hydrogen transfer: concepts and challenges. Issue 69 (6th July 2016) - Quintard, Adrien; Rodriguez, Jean
Abstract : This review summarizes the recent efforts in the development of enantioselective hydrogen transfer initiated transformations. Abstract : Hydrogen transfer initiated processes are eco-compatible transformations allowing the reversible OFF ↔ ON activation of otherwise unreactive substrates. The minimization of stoichiometric waste as well as the unique activation modes provided by these transformations make them key players for a greener future for organic synthesis. Long limited to catalytic reactions that form racemic products, considerable progress on the development of strategies for controlling diastereo- and enantioselectivity has been made in the last decade. The aim of this review is to present the different strategies that enable enantioselective transformations of this type and to highlight how they can be used to construct key synthetic building blocks in fewer operations with less waste generation.